2005
DOI: 10.1093/rpd/nci359
|View full text |Cite
|
Sign up to set email alerts
|

Paired-organ and other selected absorbed fraction for the Korean Reference Adult Male model

Abstract: The authors have developed a mathematical model for calculating internal radionuclide dosimetry for the Korean Reference Adult Male, and have also derived paired-organ and other selected inter-organ photon-specific absorbed fractions for this model. Each lung, kidney and adrenal gland was set as a separate source region even though each of them shares an identical physiological function with their complementary half. The thyroid gland was also set as a source region. Specific absorbed fractions (SAFs) were the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The first type was a family of analytical phantoms, where all organs and the whole human body were represented with 3D analytical equations [6][7][8][9][10]. The chemical constitution of different tissues presented in the human body was also given.…”
Section: Introductionmentioning
confidence: 99%
“…The first type was a family of analytical phantoms, where all organs and the whole human body were represented with 3D analytical equations [6][7][8][9][10]. The chemical constitution of different tissues presented in the human body was also given.…”
Section: Introductionmentioning
confidence: 99%
“…Such error may be avoided only when SAFs are estimated for counterpart organs separately. Kim et al 31 previously reported such differences in the SAF values of counterpart organs in Korean human mathematical phantom.…”
Section: Ivc Cross-irradiation Of Unpaired and Paired Organs For Lomentioning
confidence: 91%
“…Generally, three main types of widely used phantoms would be (1) analytical, (2) voxel, and (3) mesh-type phantoms. The human organs in analytical phantoms are defined using 3-dimensional (3D) analytical equations (Zankl et al 1992; Yamaguchi 1994; Chou et al 2003; Kim et al 2006). On the other hand, human organs in voxel phantoms are defined using a large number of small elements (i.e., volume-pixels) (Xu et al 2000; Caon 2004).…”
Section: Introductionmentioning
confidence: 99%